Drug-Related Lymphedema: Mysteries, Mechanisms, and Potential Therapies - Pal, Soumiya; Rahman, Jenat; Mu, Shengyu; Rusch, Nancy J.; Stolarz, Amanda J. (Frontiers in Pharmacology, 2022)
The lymphatic circulation is an important component of the circulatory system in humans, playing a critical role in the transport of lymph fluid containing proteins, white blood cells, and lipids from the interstitial space to the central venous circulation. The efficient transport of lymph fluid critically relies on the rhythmic contractions of collecting lymph vessels, which function to “pump” fluid in the distal to proximal direction through the lymphatic circulation with backflow prevented by the presence of valves. When rhythmic contractions are disrupted or valves are incompetent, the loss of lymph flow results in fluid accumulation in the interstitial space and the development of lymphedema. There is growing recognition that many pharmacological agents modify the activity of ion channels and other protein structures in lymph muscle cells to disrupt the cyclic contraction and relaxation of lymph vessels, thereby compromising lymph flow and predisposing to the development of lymphedema. The effects of different medications on lymph flow can be understood by appreciating the intricate intracellular calcium signaling that underlies the contraction and relaxation cycle of collecting lymph vessels. For example, voltage-sensitive calcium influx through long-lasting (“L-type”) calcium channels mediates the rise in cytosolic calcium concentration that triggers lymph vessel contraction. Accordingly, calcium channel antagonists that are mainstay cardiovascular medications, attenuate the cyclic influx of calcium through L-type calcium channels in lymph muscle cells, thereby disrupting rhythmic contractions and compromising lymph flow. Many other classes of medications also may contribute to the formation of lymphedema by impairing lymph flow as an off-target effect. The purpose of this review is to evaluate the evidence regarding potential mechanisms of drug-related lymphedema with an emphasis on common medications administered to treat cardiovascular diseases, metabolic disorders, and cancer. Additionally, although current pharmacological approaches used to alleviate lymphedema are largely ineffective, efforts are mounting to arrive at a deeper understanding of mechanisms that regulate lymph flow as a strategy to identify novel anti-lymphedema medications. Accordingly, this review also will provide information on studies that have explored possible anti-lymphedema therapeutics.